Hell and back - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2022)
"What if you woke up lying in the middle of the street in the infamous town of Fort Pratt, Montana, where thirty, young Native boys perished in a tragic 1896 boarding school fire? What if every person you encountered in that endless night was dead? What if you were covered in blood and missing a bullet from the gun holstered on your hip? What if there was something out there in the yellowed skies--along with the deceased and the smell of ash and dust--something the Northern Cheyenne refer to as the Éveohtsé-heómėse, the Wandering Without, the Stealer of Souls? What if the only way you know who you are is because your name is printed in the leather sweatband of your cowboy hat, and what if it says your name is Walt Longmire--but you don't remember him. In Hell & Back, the eighteenth installment of the Longmire series, author Craig Johnson takes the beloved sheriff to the very limits of his sanity to do battle with the most dangerous advisory he's ever faced--himself"--